2000
DOI: 10.1063/1.373324
|View full text |Cite
|
Sign up to set email alerts
|

Structure and magnetic properties of melt-spun PrFe10Mo2Nx compounds

Abstract: The structure and magnetic properties of PrFe10Mo2Nx compounds prepared by melt spinning have been investigated. A single-phase structure of ThMn12-like has been obtained in ribbons quenched at velocities vs below 40 m/s. The desired ThMn12 structure is considerably more stable for Pr(Fe, Mo)12 compounds than for Nd(Fe, Mo)12 compounds. Only at higher speeds than 50 m/s the PrFe10Mo2 ribbons quench into TbCu7-like compound of which Curie temperature is about 580 K. Annealing temperatures in excess of 1023 K ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Studies have found that many kinds of materials are capable of reversibly embedding and extracting Li-ions, thus have the potential to be anode for LIBs. According to charging/dicharging mechanism, they can be mainly classified into three kinds: intercalation/alloying/conversion materials [40]. The schematic diagram of their reaction mechanism with lithium ion is indicated in fig.…”
Section: Anode Materials For Libsmentioning
confidence: 99%
“…Studies have found that many kinds of materials are capable of reversibly embedding and extracting Li-ions, thus have the potential to be anode for LIBs. According to charging/dicharging mechanism, they can be mainly classified into three kinds: intercalation/alloying/conversion materials [40]. The schematic diagram of their reaction mechanism with lithium ion is indicated in fig.…”
Section: Anode Materials For Libsmentioning
confidence: 99%